The witches on the pendle - Akinyemi, Rowena (Oxford Univ. Press, 1997)
In 1612, near Pendle Hill in Landcashire, lived a girl called Jennet Device. She was inine years old then, poor, thin, and hungry. She has no shoes, no coat, and sometimes nothing to eat for days. Life was not easy for Jenner Device. And her grandmother, Old Demdike, was a witch. Her mother Elizabeth was a with, and her sister Alizon. Even her poor stupid brother James was a witch... Or that is what the villagers believed. This is Jennet's story or her family. It begins in 1634, when Jennet is a Prisoner in Landcaster Castle...